Open Signals and Systems Laboratory Exercises - Bolstad, Andrew K.; Dickerson, Julie A. (Open textbook library., 2021)
Open Signals and Systems Laboratory Exercises is a collection of lab assignments that have been used in EE 224: Signals and Systems I in the Department of Electrical and Computer Engineering at Iowa State University. These lab exercises have been curated, edited, and presented in a consistent format to improve student learning.